Pemanfaatan Limbah Kulit Durian sebagai Bahan Pengganti Kapas atau Dakron Bersama Komunitas Kapuk Durian - Suria Ningsih; Fitri Rahayu (Universitas Islam Negeri Sumatera Utara, 2021)
AbstractDurian skin which is known to be just waste can actually be processed into something very useful, such as turning it into a substitute for cotton or dacron. Researchers see creative innovations regarding the use of durian skin on the environment, especially for young people to take this opportunity. Self-empowerment of children is absolutely necessary to educate and prepare the nation's next generation so that they can live an entrepreneurial spirit. This community service uses the Participatory Action Research (PAR) method. The training in this activity is the procedure for processing durian skin waste into cotton or pillow stuffing. The results of community service activities, namely children or adolescents in the Garu VI environment still need information, assistance and care from the surrounding community. The role of academics becomes important as a bridge to cut the information gap.